Breeding range extension of the Peregrine Falcon (Falco peregrinus L.) in the Pannonian Plain - Rajković, Draženko; Vračarić, Miroslav (Zenodo, 2020)
During three consecutive winter/spring seasons in the period 2018-2020, the breeding territory of Peregrine Falcon was monitored at an abandoned quarry on Fruška Gora Mt., (UTM DR 00; 45.165527 N, 19.803396 E) at Vojvodina Province, Northern Serbia. Described record represents the first confirmed nesting of Peregrine Falcon in this part of the country and provides evidence of the further expansion of breeding distribution range of this species in the Pannonian Plain.